The Influence of Entrepreneurial Characteristics and Product Innovation on Business Performance in Culinary SMEs in Bandar Lampung - Vicky Andrean; Ribhan (Journal of Innovative and Creativity, 2025)
This study aims to examine the influence of entrepreneurial characteristics and product innovation on business performance in culinary MSMEs in Bandar Lampung. Culinary MSMEs are a sector that continues to grow and is a major driver of economic growth. However, the performance of a business is not only determined by external factors, but is also greatly influenced by the characteristics of business actors and their ability to innovate products. This study uses a quantitative approach with a questionnaire distribution method analyzed using SPSS with the object of research being the owners of MSMEs in the culinary sector in Bandar Lampung. The source of research data is primary data, data collection is carried out by distributing questionnaires distributed to 120 owners of MSMEs in the culinary sector in Bandar Lampung, the sampling technique used in this study is Convenience sampling. Data collection used The analysis technique used is simple linear regression to determine how much influence each independent variable, namely entrepreneurial characteristics and product innovation, separately has on the dependent variable, namely business performance. The results of the study show that entrepreneurial characteristics partially have a significant effect on business performance. Then the product innovation variable partially has a significant effect on business performance.